(untitled) (Yangi O’zbekistonda Tabiiy va Ijtimoiy-gumanitar fanlar respublika ilmiy amaliy konferensiyasi, 2025)
This study presents the surface morphology and elemental composition analysis of the DGTC+PAF ion exchanger using Scanning Electron Microscopy (SEM) and Energy Dispersive X-ray Spectroscopy (EDX). The analysis was conducted to assess the structural properties and elemental content that influence the material’s efficiency in ion exchange and selective sorption.